The Role of Immune Modulation in Pathogenesis of IgA Nephropathy - Chang, Sheng; Li, Xiao-Kang (Frontiers in Medicine, 2020)
IgA nephropathy (IgAN) is the most prevalent primary glomerulonephritis worldwide. It is a clinical-pathological syndrome, with diverse clinical manifestations characterized by recurrent gross hematuria or microscopic hematuria, and pathological changes featuring in poorly O-galactosylated IgA1 deposition in the glomerular mesangium. Pathogenesis has always been the focus of IgAN study. Across half a century of research, most scholars approve that IgAN is a group of clinical-pathological syndromes with certain common immunopathological characteristics, and multiple mechanisms are involved in its pathogenesis, including immunology, genetics, and environmental or nutritional factors. However, the precise pathogenetic mechanisms have not been fully determined. The hypothesis related to the pathogenesis of IgAN suggests that immunological factors are engaged in all aspects of IgAN development and play a critical role. A variety of immune cells (e.g. Dendritic cells, NK cells, macrophages, T-lymphocyte subsets, and B-lymphocytes, etc.) and molecules (e.g. IgA receptors, Toll-like receptors, complements, etc.) in innate and adaptive immunity are involved in the pathogenesis of IgAN. Moreover, the abnormality of mucosal immune regulation is the core of the IgAN immunopathogenesis. The roles of tonsil immunity or intestinal mucosal immunity, which has received more attention in recent years, are supported by more and more evidence. In this review, we will explore the latest progression, novel insights on immune modulation in the pathogenesis of IgAN. With better understanding of immunopathogenesis of IgAN, emerging therapies will soon become a reality in the future.